The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/nur.4770090209
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of patients with schizophrenia toward taking medication

Abstract: The attitude of 50 hospitalized persons with schizophrenia toward taking their medication was examined. Both open-ended and fixed-response estimates of attitude were made. Insight also was measured, and the relationships between insight and attitude and between hallucinations and insight were analyzed. Patients were able to provide information about beliefs and feelings about taking medication and about insight toward illness and treatment. Attitudes varied, and both strongly positive and strongly negative bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 29 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Some studies have mentioned that persons with schizophrenia expressed that they took their medication because they felt forced to by their family or to please their family (Davidhizar et al . ; Roe et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have mentioned that persons with schizophrenia expressed that they took their medication because they felt forced to by their family or to please their family (Davidhizar et al . ; Roe et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Donohoe (2006) and Pinikahana et al (2002) also showed that the level and nature of family involvement is generally associated with positive outcomes in treatment adherence. Some studies have mentioned that persons with schizophrenia expressed that they took their medication because they felt forced to by their family or to please their family (Davidhizar et al 1986;Roe et al 2009). In the present study, the participants expressed that they were motivated to maintain medication due to their family support, which they described as being accepting and caring.…”
Section: Discussionmentioning
confidence: 99%
“…However, different patient groups appear to get insufficient answers. One such group is represented by psychiatric patients ( Davidhizar et al . 1986 , Hansson 1989), although it has been called into question whether psychiatric patients are capable of understanding the information they receive and whether that information actually serves to increase rather than relieve their anxiety ( Brown et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rating scales may help in establishing a baseline of the patient's knowledge and attitudes. Assessment tools include`Knowledge of Medication' (Davidhizar & McBride 1985) and`Attitude Toward Medication' (Davidhizar et al 1986). In order to customize the nursing approach a compliance-orientated history can be established (Cameron 1996).…”
Section: Practice Implications Assessmentmentioning
confidence: 99%